A retrospective study of sodium hypochlorite pulpotomies in primary molars - Tzu-Ying Li; Li-Chuan Chuang; Aileen I. Tsai (Elsevier, 2016)
Background/purpose: Formocresol has been a popular pulpotomy medicament for primary molars, however, its toxicity and potential carcinogenicity leaves room for other alternatives such as sodium hypochlorite (NaOCl). The purpose of this study is to evaluate the clinical and radiographic success rate of 5% NaOCl pulpotomy in primary molars. Materials and methods: A retrospective research of patient records from January 1, 2009 and December 31, 2012 was conducted to evaluate the clinical and radiographic success rate of 5% NaOCl pulpotomy in primary molars. Results: A total of 147 NaOCl primary molar pulpotomies in 52 patients were included in the study. Clinical success rates at 6 months, 12 months, and 24 months were 100%, 97%, and 97%, respectively. Radiographic success rates at 6 months, 12 months, and 24 months were 99%, 89%, and 77%, respectively. Internal root resorption was the most common radiographic pathologic finding. Conclusion: The clinical and radiographic success rate for NaOCl pulpotomies is comparable with formocresol and ferric sulfate pulpotomy success rates reported in previous studies.